Peningkatan Keterampilan Pemuda Gereja Berbasis Teknologi Visual Pada Pelayanan Ibadah di HKBP Perumnas Mandala Kec. Medan Denai Provinsi Sumatera Utara - HS, Samaria Chrisna; Siagian, Sinta Marito; Tampubolon, Ferdinan Rinaldo; Ginting, Agustina; Saragih, Yessy Dea Sylvia (LPPM ITB AAS Indonesia Surakarta, 2025)
The development of science and technology really supports every human activity which makes it easier to carry out activities such as the use of visual technology such as the use of the Infocus text viewer. This Program aims to provide knowledge and increase skills in the application of visual technology and the use of the Easy Worship application in the implementation of worship activities at the HKBP PERUMNAS Mandala church to the young people of the church. This activity can improve the skills of church youth in carrying out worship services with a more efficient budget for providing church worship paper. The method used in this activity will begin with an introduction to the EasyWorship (EW) Software and training on the use of this technology and its application in displaying worship services on the EW Software. This training was carried out using group discussion methods and mentoring by the implementation team. Based on this activity, participants were able to understand the application and use of it on laptops. Furthermore, in terms of increasing innovation and creativity of HKBP Mandala youth, the implementing team carried out the activity of handing over goods to the church management.